KONSEP DASAR ETIKA KEGURUAN - Murni Saniyah; Ahmad Sarkowi; Lasman Azis; Salman Salman (Jurnal Al-Karim : Jurnal Pendidikan, Psikologi dan Studi Islam, 2023)
Teaching ethics serves as the moral foundation that governs the behavior and actions of educators in carrying out their duties. This article presents the fundamental concepts of teaching ethics, encompassing moral, professional, and social responsibility aspects. The discussion includes key principles such as justice, integrity, and character development, along with the application of these values in the teaching process. Instrument used in the performance evaluation is the assessment scale (rating scale). Furthermore, the article highlights the significance of self-reflection for teachers to continuously enhance their moral quality and professionalism. Teaching ethics is not merely a set of formal norms but also a foundation shaping positive relationships between teachers, students, and the community.